WAYS OF ACQUISITION AND COMPREHENSION OF IMPLICIT MEANING BY PRIMARY SCHOOLCHILDREN WITH AUTISM - Branytska, Maryna (International Journal of Innovative Technologies in Social Science, 2020)
The article deals with ways of perceiving verbal means of communication, specific of children with autism. The results of the complex psychological-pedagogical diagnostics of the impressive speech, characteristic of the children with Autism Spectrum Disorder (ASD), have been analyzed. One of the effects of the ASD in children is specific development of their communication sphere. We have described the results of investigating the passive vocabulary; understanding of instructions; text comprehension; understanding of the implicit meanings of words, phrases and texts. While doing the research we found out that unlike normally developed pupils, those with ASD had a difficulty in establishing the contact with a researcher. Not being able to conceptualize the environment fully children with ASD have low interest in communication. Considerable problems with socializing of children with ASD are seen in their inability to establish contact with adults and peers. Therefore there is a need of looking for individual approaches to restore communication.The results of the research have shown that children with autism difficulties of switching attention while performing the tasks. Prepositions and personal pronouns cause difficulties as their understanding has not been well-formed. The investigation has shown that pupils with autism understand and use synonyms in their learning process appropriately but antonyms are hard for them to grasp. It has been noticed that homonyms are understood only in a certain context that is caused by a low flexibility of thinking. In case of their correct order and use the positive results become possible.